LITERATUR REVIEW: TERAPI NON FARMAKOLOGIS DISMINOREA - TRIWAHYUNIASTUTI; Wahyuningsih Wahyuningsih (STIKES Estu Utomo, 2025)
Non-pharmacological therapy can be used as a substitute for pharmacological therapy for primary dysmenorrhea such as warm compresses, drinking tamarind turmeric, effleurage massage, music therapy, giving red ginger, consuming coconut water, using avocado juice, carrot juice, boiled papaya leaves and using lavender therapeutic oil.Conclusion: Non-pharmacological therapy has been proven to be effective in reducing dysmenorrhoea pain and its use can take into account the conditions and availability in our environment.Non-pharmacological therapy has been proven to be effective in reducing dysmenorrhoea pain and its use can take into account the conditions and availability in our environment.